Carcinoma of the nasopharynx in Chiang Mai University Hospital: a review of 205 cases - Sumitsawan Y. (2014)
Carcinoma of the nasopharynx is one of the common head and neck cancers in Southeast Asia. We had studied 205 cases of nasopharyngeal cancer who attended the ENT clinic of the Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand from 1980-1984. The majority of the patients were found in stage IV. One hundred and five patients received a curative dose of radiation therapy. The observed actuarial 5 year survival was 34 per cent. There was a significant decrease in survival of patients with T4 disease. Differences in age, sex, histopathology and N-stage did not affect the survival. So far, the only specific treatment we can offer patients is radiation therapy, so an earlier diagnosis must be established in order to get better results of treatment.